2019
DOI: 10.1101/gad.331850.119
|View full text |Cite
|
Sign up to set email alerts
|

Ways to unwind with HROB, a new player in homologous recombination

Abstract: Homologous recombination (HR) is an important route for repairing DNA double-strand breaks (DSBs). The early stages of HR are well understood, but later stages remain mysterious. In this issue of Genes & Development, Hustedt and colleagues (pp. 1397-1415) reveal HROB as a new player in HR required for recruitment of the MCM8-9 complex, which is paralogous to the MCM2-7 replicative helicase. HROB functions closely with MCM8-9 to promote postsynaptic DNA repair synthesis. This study sheds valuable light on late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Substantive results revealed that MCM8 and MCM9 play a vital role in HR repair as MCM8-9 complex. 126 Lee et al 127 found that incapable mutation of MCM8-9 complex could not recognize MRN complex, leading to degressive HR efficiency. Moreover, some research proved that the depletion of MCM9 is attributed to reduced proliferation, which may be modulated by ATM-CHK2 pathway.…”
Section: Base Mismatch a T T A C Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantive results revealed that MCM8 and MCM9 play a vital role in HR repair as MCM8-9 complex. 126 Lee et al 127 found that incapable mutation of MCM8-9 complex could not recognize MRN complex, leading to degressive HR efficiency. Moreover, some research proved that the depletion of MCM9 is attributed to reduced proliferation, which may be modulated by ATM-CHK2 pathway.…”
Section: Base Mismatch a T T A C Gmentioning
confidence: 99%
“…Substantive results revealed that MCM8 and MCM9 play a vital role in HR repair as MCM8‐9 complex. 126 Lee et al. 127 found that incapable mutation of MCM8‐9 complex could not recognize MRN complex, leading to degressive HR efficiency.…”
Section: The Replication Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Most reports to date suggest that MCM8-9 functions in meiosis and in DNA repair, particularly in homologous recombination (HR) in response to DNA interstrand crosslinks (ICLs), as well as to maintain replication fork stability 17,18,22,[32][33][34][35][36] . Mutant cell lines show only minor sensitivity to ionizing radiation or bleomycin, suggesting that MCM8-9 is not a universal DNA break repair factor 37,38 . Rather, MCM8-9 may function in recombination assisting ICL repair in the context of stalled replication forks, possibly alongside Fanconi anemia proteins [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…RAD51 coats the ssDNA to form a nucleoprotein filament which searches for sequence homology in the intact chromatid, invades the homologous duplex and directs annealing to the homologous sequences. The invading strand is then extended using a form of non-canonical DNA synthesis (Bonilla et al ., 2020; Saredi & Rouse, 2019). The final stages of HR can result in the formation of structures that entangle the two chromatids, which are enzymatically removed to complete repair (Lilley, 2017).…”
Section: Introductionmentioning
confidence: 99%